EFEKTIVITAS INSTAGRAM @KOMINFODIY SEBAGAI SUMBER INFORMASI AKTUAL TENTANG COVID-19 - Rustono Marta; Mufid Salim; Silvia Indah Permatasari (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
The purpose of this study was to determine the effectiveness of Instagram @kominfodiy as a communication medium in providing information about COVID-19. This study uses a quantitative research approach using a questionnaire to the people of Yogyakarta with a total of 110 respondents. Based on the research results, it can be concluded that the magnitude of the influence of Instagram media is about 0.542, which means that the significant contribution given by the Instagram media variable as a medium of information to communication media is 54.2%. Instagram media by regularly uploading information posts is an effective way for @kominfodiy to provide information about COVID-19 to the public. The correlation test results explain that there is a relationship between the variable (X) and the dependent variable (Y) with a total value of 0.736. The significance value from the coefficient table is 0.000, where the value is smaller than 0.05 (0.000 < 0.05). Keywords: Instagram effectivity, communication media, COVID-19,